2006
DOI: 10.7326/0003-4819-144-10-200605160-00007
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: Glomerulonephritis in Patients with Hepatitis C Cirrhosis Undergoing Liver Transplantation

Abstract: Immune-complex glomerulonephritis was common in patients with end-stage HCV-induced cirrhosis and was often clinically silent. Its potential to cause renal failure after liver transplantation may be underappreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 12 publications
2
92
0
3
Order By: Relevance
“…Furthermore, a recent study of patients who underwent protocol renal biopsy at the time of liver transplantation for HCVassociated liver failure found that most of these patients (25 of 30 patients) had an immune complex-mediated glomerulonephritis, which was often clinically unsuspected (33). This points to a potential major contributing cause of renal failure that may occur after transplant in these patients and suggests that the patient group with clinically evident HCV-associated glomerular injury may be akin to the tip of an iceberg.…”
Section: Hepatitis C Virus-associated Glomerulonephritismentioning
confidence: 99%
“…Furthermore, a recent study of patients who underwent protocol renal biopsy at the time of liver transplantation for HCVassociated liver failure found that most of these patients (25 of 30 patients) had an immune complex-mediated glomerulonephritis, which was often clinically unsuspected (33). This points to a potential major contributing cause of renal failure that may occur after transplant in these patients and suggests that the patient group with clinically evident HCV-associated glomerular injury may be akin to the tip of an iceberg.…”
Section: Hepatitis C Virus-associated Glomerulonephritismentioning
confidence: 99%
“…Liver recipients are among the most likely to develop renal insufficiency after transplantation. Curtis's University of Alabama at Birmingham group performed protocol kidney biopsies in 30 patients who had hepatitis C and normal renal function and underwent liver transplantation (53). Twenty-five (83%) had significant preexisting glomerular pathology.…”
Section: Alternatives To An Incomplete Paradigmmentioning
confidence: 99%
“…We suggest that a native kidney biopsy should be performed whenever possible to assist in the diagnosis of renal failure and gauge the risk for development of recurrent disease (8 -10). Liver transplant recipients, in particular, seem to have a high frequency of glomerular abnormalities without significant clinical or biochemical evidence of renal dysfunction (11,12).…”
Section: Discussionmentioning
confidence: 99%